Identify Factors That Influence Hard Skill Competency and Soft Skill Competency Through the Quality of Teaching in Aviation Vocational Education - Suyatmo Suyatmo; Ekohariadi Ekohariadi; Arie Wardhono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research analyzes factors influencing quality teaching to create complex skill competency (HSC) and soft skill competency (SSC) in education vocational graduates. Aviation vocational education produces aviation experts who can compete in the era of the global market. HSC is a technical skill, and SSC is an individual's interpersonal skill. The quality of vocational teaching has a vital role in creating graduate performance. Method: This research studies quantitative with a survey method. Samples are Aircraft Engineering students - Aviation Polytechnic in Indonesia, as many as 229 people—data retrieval using instrument research that has been fulfilled with validity and reliability tests. Analysis of research data uses Structural Equation Modeling (SEM). Result: This research shows that the formation performance of graduates (HSC and SSC) is determined by quality teaching. Lecturer Characteristics, Teaching Methods, and Laboratory Technicians are essential for increasing teaching quality in the formation of HSC—currently, SSC is developing through the pattern parenting student method. Students' success, integrity, and interpersonal skills reflect SSC. So that graduates are ready to compete in the job market. Novelty: Develop lecturers' characteristics and laboratory technicians to significantly increase the quality of education and prepare students to enter the world of work with relevant skills.